Replanting Thresholds for Soybean Using Two‐ and Four‐Week Plant Survival Metrics. (1st March 2016) - Weeks, Weston; Popp, Michael; Rupe, John; Rothrock, Craig; Ross, Jeremy; Steger, Adele
Abstract : The rising cost of seed is causing soybean [ Glycine max (L.) Merr.] producers to reconsider seeding rates and replanting decisions. Data were collected at two sites, over 5 yr, three planting dates, three seeding rates, and with or without seed treatment. Information on stand counts, the number of established plants at 2 and 4 wk after planting, and yield was used to assess whether profit‐maximizing replanting stand count thresholds differ depending on how long a producer waits to decide to replant. Because planting date negatively affects yield potential and higher seeding rates are recommended for late‐season plantings, delayed planting is tantamount to higher cost and lost yield potential. To measure how replanting thresholds are affected by changes in important decision variables, soybean seed cost, soybean price, and replanting equipment costs were varied. Results suggest that (i) seed treatment is cost effective, (ii) replanting stand count thresholds relative to profit‐maximizing stand counts are quite low because replanting costs are high and soybean can compensate for low stand counts without excessive yield loss, (iii) these replanting thresholds vary whether the decision is made 2 or 4 wk after planting depending on soil texture, yield potential, and seeding rates of the replanted soybean; (iv) optimal planting dates vary by location; (v) variation in soybean price and seed cost have a larger impact than the range of replanting equipment costs on replanting thresholds; and (vi) replanting decisions may be made earlier than the current recommendation of waiting until 4 wk after planting.